Security in Vehicular Networks: Focus on Location and Identity Privacy - Benarous (Wiley Data and Cybersecurity, 2022)
Monograph
fulltext
Keywords: Computing and Processing; Communication, Networking and Broadcast Technologies; Transportation; Signal Processing and Analysis; Robotics and Control Systems